Conditional generalized analytic Feynman integrals and a generalized integral equation - Seung Jun Chang (International Journal of Mathematics and Mathematical Sciences, 2000)
We use a generalized Brownian motion process to define a generalized Feynman integral and a conditional generalized Feynman integral. We then establish the existence of these integrals for various functionals. Finally we use the conditional generalized Feynman integral to derive a Schrödinger integral equation.